Analysis of Factors Influencing the Success of Exclusive Breastfeeding at the Ujung Batu Health Center, North Padang Lawas Regency - Rambe, Novrida Sari; Efendy, Ismail; Fitria, Aida (PROMOTOR, 2025)
Background: Exclusive breastfeeding is an important factor in supporting the growth and development of babies. However, exclusive breastfeeding coverage is still low in various regions, including at the Ujung Batu Health Center, North Padang Lawas Regency. Research Objectives: To analyze the factors that affect the success of exclusive breastfeeding. Research Method: Using the Analytical Survey method with a Cross Sectional approach. Research Population: this is all mothers who have babies 6-12 months in the Ujung Batu Health Center as many as 115 people and a sample of 89 people with random sampling techniques. Research Instrument: this is a questionnaire about the success of Exclusive Breastfeeding and several factors related to the success of Exclusive Breastfeeding using univariate, bivariate analysis with chi-square test and multivariate with logistic regression. Data were collected through questionnaires and analyzed using logistic regression tests. The results of the study: showed that the factors that had a significant influence on the success of exclusive breastfeeding were the level of maternal knowledge (p=0.002), family support (p=0.005), the role of health workers (p=0.001), and maternal employment factors (p=0.010). Mothers with a good level of knowledge and strong family support are more likely to breastfeed exclusively. In addition, health workers who actively provide education increase the likelihood of success in exclusive breastfeeding. In contrast, working mothers have a lower likelihood of exclusive breastfeeding. The conclusion of this study is that increased education about exclusive breastfeeding as well as the support of families and health workers is very important to increase the coverage of exclusive breastfeeding in this region Suggestion: Respondents who have babies aged 6-12 months are expected to be able to give exclusive breastfeeding and can increase awareness of the importance of exclusive breastfeeding, and have high patience when breastfeeding exclusively.